Genetic and Biochemical Characterization of a Novel umuD Mutation: Insights into a Mechanism for UmuD Self-Cleavage - Sutton, Mark D. (American Society for Microbiology, 2001)
Most translesion DNA synthesis (TLS) in Escherichia coli is dependent upon the products of the umuDC genes, which encode a DNA polymerase, DNA polymerase V, with the unique ability to replicate over a variety of DNA lesions, including cyclobutane dimers and abasic sites. The UmuD protein is activated for its role in TLS by a RecA–single-stranded DNA (ssDNA)-facilitated self-cleavage event that serves to remove its amino-terminal 24 residues to yield UmuD′. We have used site-directed mutagenesis to construct derivatives of UmuD and UmuD′ with glycines in place of leucine-101 and arginine-102. These residues are extremely well conserved among the UmuD-like proteins involved in mutagenesis but are poorly conserved among the structurally related LexA-like transcriptional repressor proteins. Based on both the crystal and solution structures of the UmuD′ homodimer, these residues are part of a solvent-exposed loop. Our genetic and biochemical characterizations of these mutant UmuD and UmuD′ proteins indicate that while leucine-101 and arginine-102 are critical for the RecA-ssDNA-facilitated self-cleavage of UmuD, they serve only a minimal role in enabling TLS. These results, and others, suggest that the interaction of RecA-ssDNA with leucine-101 and arginine-102, together with numerous other contacts between UmuD(2) and the RecA-ssDNA nucleoprotein filaments, serves to realign lysine-97 relative to serine-60, thereby activating UmuD(2) for self-cleavage.